A green approach for the multicomponent synthesis of polyhydroquinolines and 6-unsubstituted dihydropyrimidinones using novel highly proficient acidic ionic liquid [CEMIM][MSA] as a reusable catalyst - Priyanka Patil; Suresh Kadam; Dayanand Patil; Paresh More (Catalysis Communications, 2022)
Carboxylic acid functionalized imidazolium based novel acidic ionic liquid [CEMIM][MSA] was synthesized using economically feasible raw materials under very mild condition. The cost effective and sustainable synthesis of polyhydroquinoline and 6-unsustituted dihydropyrimidinone derivatives in green media was first time carried out very effectively using [CEMIM][MSA] catalyst. Acidic ionic liquid catalyst [CEMIM][MSA] with carboxylic acid group was easily separated and reused up to five cycles without much loss in its catalytic activity and stability. The introduced catalyst had showed a better catalytic performance in aqueous medium to obtain described compounds with excellent yields in shorter time. Purification free isolation of pure polyhydroquinolines and 6-unsustituted dihydropyrimidinones derivative makes the revealed protocol attractive and ecological.